Metody graficzne w analizach porównawczych systemów wartości - Czerniawska, Mirosława; Nazarko, Joanicjusz; Rybaczuk, Mikołaj (Graphical Methods in Comparative Studies of Value Systems, 2005)
The paper concerns a comparative study of value systems carried out on 644 students of Polish and Russian high schools. Factors such as nationality, gender field of education have been taken into consideration. The paper proves the usefulness of graphic methods in such analyses, one of the reasons being the increased efficiency of human mind in information processing. Authors of the study have applied a graphic method that presents the structure of multidimensional data on the plane. This has allowed for a multi-perspective view of the studied value systems and an in-depth interpretation of the research results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 283-292